Designing research in education concepts and methodologies - Swain, Jon 1954- (SAGE, 2017)
"This is a clear introduction to the methodological and philosophical debates in the field of education research. It sets out the key ideas, questions, and dilemmas which inform all research and then, through the careful use of case studies and practical advice from experienced researchers, grounds them in the specific concerns of education and educational studies. Written by experienced academics and teachers the book links broad philosophical principles with practical strategies for designing and conducting ethical and effective research."--Publisher's website.